Zakres regulacji statutu samorządu załogi przedsiębiorstwa - Sowiński, Roman (Wydział Prawa i Administracji UAM, 1988)
The author, having presented and characterized the most important problems which should be analysed while determining legal character of a statute of a self-government of an enterprise crew focuses his attention on the range of statutory regulation and on ties linking the self-government statute with the Act of the Diet (Sejm). According to the author the said ties may be described as a) the relation of transferring, b) the relation of complementing c) the relation of developing, and d) the relation of free regulation. A self-government statute cannot be treated as an executory act to only one Act of the Diet. It may contain provisions referring to different Acts, all of them forming sui-generis „self-government law". The author classifies statutes from the point of view of methods of determining the range of statutory regulation. He distinguishes between several separate types of statutes, from „closed" ones — the contents of which is established exclusively by a legislator, to „open" statutes — with the contents shaped freely by the subject laying down the statute. The article presents the conception of treating an enterprise statute and a statute of a self-government of an enterprise crew as a „union of two equivalent organizational acts". The author offers arguments for the above standpoint. In his opinion the Acts of September 1981 form a „new quality" in the field of internal regulation of enterprises.
The regulation range of a statute of an enterprise crew self-government